Distinct Progenitor Origin Distinguishes a Lineage of Dendritic-Like Cells in Spleen - Petvises, Sawang; O'Neill, Helen C. (Frontiers in Immunology, 2014)
The dendritic cell (DC) compartment comprises subsets of cells with distinct phenotypes. Previously this lab reported methodology for hematopoiesis of dendritic-like cells in vitro dependent on a murine splenic stromal cell line (5G3). Co-cultures of lineage-depleted bone marrow (Lin− BM) over 5G3 continuously produced a distinct population of dendritic-like “L-DC” for up to 35 days. Here the progenitor of L-DC is investigated in relation to known BM-derived hematopoietic progenitors. It is shown here that L-DC-like cells also derive from the CD150+Flt3− long-term reconstituting-hematopoietic stem cells (HSC), and also from the Flt3+ multipotential progenitor subset in BM. Lin− BM co-cultures also produce a transient population of cells resembling conventional (c) DC. Production of cDC-like cells is shown here to be transient and M-CSF dependent, and also appears following co-culture of described common dendritic progenitors or monocyte dendritic progenitors over 5G3. BM cells from C57BL/6-flt3Ltm1lmx and C57BL/6-Csf2tm1Ard mice which lack cDC precursors and monocytes, are shown here to contain L-DC progenitors which can seed 5G3 co-cultures. L-DC are functionally distinct cells, in that they arise independently of M-CSF, and by direct differentiation from HSC.